G534(P) A model for city-wide implementation of intensive behavioural intervention to improve sleep in vulnerable children. (May 2019) - Elphick, HE; Hall, L; Dawson, V; Lawson, C; Siddall, S; Ives, A; Reynolds, J; Kingshott, RN
Abstract : Aim: A partnership involving a Children's Trust, the City Council and a Sleep Charity evaluated a behavioural intervention to provide support to parent/carers and young people to improve sleep patterns. Methods: The intervention entailed basic education about sleep, a one-to-one session with a sleep practitioner to create an individual sleep programme and telephone support to empower the parent to carry out the sleep programme at home. Results: 39 children completed the intervention and evaluation, median age 8.56 years (range 1.82–15.75 years). 79.5% were male. 75% had a diagnosis of ADHD or were awaiting assessment, the remaining 25% were Looked After or Adopted Children (of whom 10% also had ADHD). Parents' ratings of their child's ability to self-settle to sleep improved from 1.13/10 to 6.73/10 after the intervention (MD 5.62, 95% confidence intervals 4.56–6.69, p<0.05). Children gained on average an extra 2.4 hours sleep a night. The average number of hours of sleep that the child actually got was 6.27 hours at baseline and 8.62 after the intervention (MD 2.35, 95% CI 1.64–3.06, p<0.05). There was a statistically significant improvement in time taken to settle, time to fall asleep, number and duration of night-time wakenings. The primary word used to describe the mood of the child on wakening before the intervention was 'grumpy' and after the intervention was 'happy'. The impact of sleep deprivation on the parents' wellbeing improved for all measures. The overall WEMWBS score improved significantly following the intervention (MD 8.84, 95% CI 5.32–12.36, p<0.05). There was a reduction in the number of illnesses in both parent/carers and children following the intervention. Although some parents did not find the programme helpful, 100% said they would recommend it to others. Conclusion: The evaluation gave us confidence in the delivery model. 'Regular telephone calls and support' and 'Learning about sleep' were the main positive factors. Our partnership working brought together the individual strengths, drive and passion that were critical for delivery, planning, and influencing better provision for families. We have established a strategic group to support local implementation and produced a draft delivery model which we believe is replicable for other areas.